2018
DOI: 10.5812/intjsh.58213
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Rural Elementary School Environmental Characteristics with Children’s Physical Activity Levels at School

Abstract: Background: The importance of school settings for obesity prevention efforts may be most critical in low-income rural areas where healthy eating and physical activity (PA) resources are scarce. This study examined the association of rural elementary school environmental characteristics with children's PA behaviors at school. Methods: Analyses were based on objectively measured height, weight, and PA data from 1443 first to sixth graders attending six rural elementary schools in Oregon. The School Physical Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Gunter et al 68 found that school environmental characteristics such as structured physical education, classroom‐based PA, PA messaging, and appropriate amounts of indoor and outdoor space to be physically active are all correlates of school‐day PA in rural schools. When considering rural interventions separately for our study, the two that were effective at increasing total PA included a classroom component and a physical education component, which supports the findings from Gunter et al 68 However, to increase total PA in rural youth and not just school‐day PA, a more in‐depth exploration of rural‐specific challenges needs to occur, especially because PA levels among rural youth are very low 69 and tend to be lower than that of urban youth 70 . Given the fact that this review only included five rural studies, there is clearly a need for more school‐based intervention work to be done in these settings in order to further understand both the challenges and benefits of implementing PA programs for rural youth.…”
Section: Discussionmentioning
confidence: 99%
“…Gunter et al 68 found that school environmental characteristics such as structured physical education, classroom‐based PA, PA messaging, and appropriate amounts of indoor and outdoor space to be physically active are all correlates of school‐day PA in rural schools. When considering rural interventions separately for our study, the two that were effective at increasing total PA included a classroom component and a physical education component, which supports the findings from Gunter et al 68 However, to increase total PA in rural youth and not just school‐day PA, a more in‐depth exploration of rural‐specific challenges needs to occur, especially because PA levels among rural youth are very low 69 and tend to be lower than that of urban youth 70 . Given the fact that this review only included five rural studies, there is clearly a need for more school‐based intervention work to be done in these settings in order to further understand both the challenges and benefits of implementing PA programs for rural youth.…”
Section: Discussionmentioning
confidence: 99%
“…During this stage, the physical development of school children has reached maturity and harmony, preparing the body for the pubertal developments characteristic of adolescence [26]. In addition, there are several changes in cognition that occur, such as the development of the capacity for abstraction and the development of more complex logical processes [27]. Regarding the emotional field, school children begin to suffer from affective alterations due to the onset of sexuality, as well as changes in their self-concept, their emotional perception, and the way they socialize with others.…”
Section: Introductionmentioning
confidence: 99%